Linezolid Induced Lactic Acidosis: The Side Effect, Clinician Should Be Aware of - Nightingale, Savannah (Cureus, 2020)
Linezolid is a synthetic antibiotic that functions through the inhibition of bacterial protein synthesis by binding to ribosomal ribonucleic acid (rRNA). Deliverable in both intravenous and oral form, with a low level of resistance amongst Methicillin-resistant Staphylococcus aureus (MRSA) strains, it is recommended for a wide range of gram-positive infections. We present a case of a male patient who underwent endovascular abdominal aortic aneurysm repair complicated by abdominal sepsis due to bowel ischemia; several days after linezolid therapy was initiated, he presented with signs of lactic acidosis. After excluding other sources such as metabolic, hypoxia, or organ damage, the resulting lactic acidosis was determined to be a side effect of linezolid.